Um framework interativo para validação de resultados de pesquisas de otimização baseados em heurísticas aplicadas a problemas de programação de tarefas - Oliveira, Ronaldo Castro de (2016)
When evaluating researches using heuristics and metaheuristics is perceived that there is a lack of standardization in the analysis and representation of the output results. Some works in this area presents only tabulated results with analysis based on mean and standard deviation values. Other works shows also graphs that allow a visual analysis of the results, but lacking a statistical analysis to reach conclusions. In a few works, it can be perceived the concern about in conducting a statistical analysis that can be able to provide more conclusive information, such as parametric and non-parametric analysis. This lack of standardization makes it difficult to compare related researches with the same goals. In addition, researchers are compelled to use ad-hoc approaches to demonstrate advantages and disadvantages of new techniques developed. This study proposes an implementation of a researches development process using optimization based on heuristics and meta-heuristics for solving scheduling problems of production engineering, focusing on statistical validation of output results. The validation of this process is achieved by developing implementation of a computational framework that provides support to comparison benchmarks, parameterization of algorithmic solutions analyzed, execution of the algorithmic solutions based on heuristics with storage of results and full allowance for statistical analysis from the output results.